A Horizontally Polarized Omnidirectional Antenna Using Stacked Curve Dipoles for DTV Reception - Chuwong Phongcharoenpanich; Weerayuth Polkaew; Bancha Luadang; Prayoot Akkaraekthalin (My University, 2015)
This paper presents an omnidirectional antenna using stacked curve dipoles radiating horizontal polarization for digital television (DTV) reception. The proposed antenna consists of stacked curve dipoles designed on brass sheet. The parametric study is carried out for various dimensions of curve dipoles to improve the impedance bandwidth. The results show good impedance matching forS11of less than −10 dB along the frequency range from 404 MHz to 871 MHz. The antenna gain is between −10 dBi and 0.67 dBi along the frequency range from 470 to 862 MHz.
Keywords: Curve fitting; Antenna Design and Analysis